“Propuesta de Plan de Negocios para el Laboratorio de-Gastronomía-Cafetería de la Carrera de Turismo en la Universidad Nacional de Loja” - Quizhpe Morocho, Angel Fernando (2024)
University cafeterias are a point of social and cultural interaction within the academic environment. They contribute to the general welfare of the university community, while representing a source of income and learning, especially in the context of universities that integrate Catering or Mice techniques in their educational offerings. They are designed to meet the food needs of students, teachers, administrative staff and visitors of the educational institution. The Tourism Career has its own Gastronomy Laboratory - Cafeteria in which, in addition to offering food and beverages, its infrastructure is used for special events and the development of pre-professional practices of the students of the Tourism Career. The general objective of this research work was to design the business plan for the Gastronomy-Cafeteria Laboratory, and to carry it out, two specific objectives were established: to make a diagnosis of the current state of the Gastronomy-Cafeteria Laboratory; and to propose a business plan for the Gastronomy-Cafeteria Laboratory through the Canvas Model. For the work it was necessary the application of some methods such as: analytical method, descriptive method, inductive method, deductive method and synthetic method. In the development of the first objective, we used techniques such as: direct observation for the internal and external diagnosis of the Gastronomy-Cafeteria Laboratory, the general company file (adapted for the Gastronomy-Cafeteria Laboratory) was used to gather fundamental and necessary information for the beginning of the research work, Chek list of the food and beverage tourism regulations created by the MINTUR, was applied in the internal environment of the laboratory, the surveys were directed towards the real clients of the laboratory, the interviews were conducted with the main authorities of the National University of Loja and administrators in charge of the laboratory in the Tourism Career. Furthermore, the development of the SWOT matrix which served to determine the strengths, opportunities, weaknesses and threats of the Gastronomy Laboratory - Cafeteria.